Towards optimisation of surface enhanced photodynamic therapy of breast cancer cells using gold nanoparticle–photosensitiser conjugates. Issue 3 (21st December 2017) - García Calavia, Paula; Marín, María J.; Chambrier, Isabelle; Cook, Michael J.; Russell, David A.
Abstract : Surface enhanced fluorescence of zinc pthalocyanine-functionalised gold nanoparticles leads to a remarkable enhancement in photodynamic efficiency and cell death. Abstract : Gold nanoparticles (AuNPs; ca. 4 nm) were synthesised and functionalised with a mixed monolayer of polyethylene glycol (PEG) and one of two zinc phthalocyanines (ZnPcs), the difference between the two molecules was the length of the carbon chain that connects the Pc to the gold core. The chain was composed of either three (C3Pc) or eleven (C11Pc) carbon atoms. The C11Pc photosensitiser displayed higher fluorescence emission intensity than the C3Pc in solution. By contrast, the C3Pc photosensitiser exhibited higher fluorescence when bound to the surface of the AuNPs than the C11Pc, despite the shorter carbon chain which was expected to quench the fluorescence. In addition, the C3Pc nanoparticle conjugates exhibited an enhancement in the production of singlet oxygen ( 1 O2 ). The metal-enhanced 1 O2 production led to a remarkable photodynamic efficacy for the treatment of human breast cancer cells.